POSSIBILITIES OF CHEMOEMBOLIZATION OF UTERINE ARTERIES WITH LOCALLY ADVANCED CANCER OF THE UTERINE BODY (Archive of Conferences, 2022)
To determine the effectiveness of uterine artery chemoembolization for the treatment of locally advanced cancer of the uterine body complicated by bleeding.